(untitled) (Biomedical Research and Therapy, 2023)
Research has suggested that people with polycystic ovary syndrome (PCOS) have an increased risk of developing type 2 diabetes or prediabetes before the age of 40 years. Erythema multiforme major refers to a severe generalized rash with limited desquamation and mucous membrane involvement with blister formation. This case report will help all health care professionals be aware and vigilant regarding the adverse drug reaction caused by the combination of glimepiride, voglibose, metformin, and clomiphene citrate. A female patient in her early 30s visited the outpatient department for follow-up with a history of PCOS and type 2 diabetes. Her main complaints were itching, redness, and a pink and brown skin allergy on the face, neck, shoulder, breast, abdomen, and back, along with breast tenderness or discomfort. She had been prescribed oral clomiphene citrate 100 mg, vitamin D 10,000 IU twice weekly, and calcium 1,250 mg twice daily for PCOS and a combination of glimepiride 2 mg, voglibose 0.2 mg, and metformin 500 mg SR daily for type 2 diabetes. An adverse drug reaction (ADR) was found probable based on assessment with the Naranjo scale. ADRs such as maculopapular rash following erythema multiforme major are fatal. They can cause stress and anxiety and reduce the patient's quality of life. This case will help physicians and clinicians in the early detection and management of ADRs.